Perfusable Tissue Bioprinted into a 3D-Printed Tailored Bioreactor System - Gensler, Marius; Malkmus, Christoph; Ockermann, Philipp; Möllmann, Marc; Hahn, Lukas; Salehi, Sahar; Luxenhofer, Robert; Boccaccini, Aldo R.; Hansmann, Jan (Bioengineering, 2024)
Bioprinting provides a powerful tool for regenerative medicine, as it allows tissue construction with a patient’s specific geometry. However, tissue culture and maturation, commonly supported by dynamic bioreactors, are needed. We designed a workflow that creates an implant-specific bioreactor system, which is easily producible and customizable and supports cell cultivation and tissue maturation. First, a bioreactor was designed and different tissue geometries were simulated regarding shear stress and nutrient distribution to match cell culture requirements. These tissues were then directly bioprinted into the 3D-printed bioreactor. To prove the ability of cell maintenance, C2C12 cells in two bioinks were printed into the system and successfully cultured for two weeks. Next, human mesenchymal stem cells (hMSCs) were successfully differentiated toward an adipocyte lineage. As the last step of the presented strategy, we developed a prototype of an automated mobile docking station for the bioreactor. Overall, we present an open-source bioreactor system that is adaptable to a wound-specific geometry and allows cell culture and differentiation. This interdisciplinary roadmap is intended to close the gap between the lab and clinic and to integrate novel 3D-printing technologies for regenerative medicine.
CRIS-Team Scopus Importer:2024-02-02
Keywords: 3D-printing; adipose tissue; biofabrication; bioprinting; cell culture simulation; perfusable bioreactor